Editorial - Melba Libia Cárdenas (Profile: Issues in Teachers' Professional Development)
I am very pleased to present this edition of our journal which, as always, brings about satisfaction and a variety of topics to share with our readership. As established in our mission, we are committed to gathering works by teachers of different educational levels and contexts as well as by teacher educators who engage in researching, innovating and reflecting upon English language teaching issues. The works we present do not deal with only the scientific features that should characterize an academic publication like ours, but experiences that have to do with paths travelled and stories that can be told. That is the reason for opening this editorial with Johnson and Golombek's quote.